К.РАХМАНОВТЫҢ «ЕДИГЕ» ДРАМАСЫНДА РЕМАРКАЛАРДЫҢ ХЫЗМЕТИ - Палымбетова, М. (ILIM hám JÁMIYET, 2019)
The article is devoted to the study of remarks used in the musical drama“Edige” by K.Rakhmanov, their role in the description of the heroe’s psychology, profession and actions.